A supervisory enrichment program based on flipped learning for a sample of school counseling students at the university - Mohammad Abood; ziad Alkhazaleh; Saleh Daradkeh; Rabie AL-zgool (Journal of Technology and Science Education)
Flipped learning represents an unconventional approach aimed at empowering students. This study sought to assess the impact of an enrichment supervisory program utilizing flipped learning on enhancing motivation for learning and academic achievement. The sample comprised 348 third and fourth-year students majoring in school counseling at a government university in Jordan. Among them, 40 students exhibiting low motivation and achievement levels were identified and evenly split into 20 experimental groups, taught via flipped learning, and 20 control groups, taught through traditional methods.